Sikap Bahasa Masyarakat Ciwaru terhadap Multilingualisme dalam Rangka Melestarikan Budaya di Kawasan Geopark Dunia - Murni Maulina (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
An area that has developed with multilingualism is certainly influenced by the community and the use of its language. People's attitudes towards language have an important role in preserving the culture of the area. This study aims to reveal the language attitude of the people of Ciwaru Village in the Ciletuh Geopark area towards multilingualism in order to preserve culture in the world geopark area and international tourism. This study using descriptive qualitative research design. The data collection of this research was carried out by direct interviews and distributing questionnaires to the people of Ciwaru Village, so that the data was in the form of responses or answers from the community. The research findings are that the people of Ciwaru Village have a positive attitude towards the three languages found in the Ciletuh Geopark Area. The community contributes to preserving the language as part of the culture by showing an attitude of language loyalty, language pride, and awareness of language. Research on community language attitudes towards multilingualism in the Ciletuh Geopark Area has never been done, so the results of this study are the first research to reveal the positive attitudes of the people of Ciwaru Village towards Sundanese, Indonesian, and English in the area.